63.1k views
4 votes
G(x) = x3 - 4
h(x) = x2 + 2
Find h(-2) - g(-1)

User Ejgottl
by
5.4k points

1 Answer

2 votes

Answer:

11

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

g(x) = x³ - 4

h(x) = x² + 2

h(-2) is x = -2

g(-1) is x = -1

Step 2: Find h(-2) - g(-1)

  1. Substitute: ((-2)² + 2) - ((-1)³ - 4)
  2. Exponents: (4 + 2) - (-1 - 4)
  3. Add/Subtract: 6 - (-5)
  4. Subtract: 11
User Hazem Essam
by
5.9k points